2011
DOI: 10.1007/s00542-011-1326-7
|View full text |Cite
|
Sign up to set email alerts
|

The development of two-component micro powder injection moulding and sinter joining

Abstract: Two-component micro powder injection moulding experienced significant progress in the recent past. Starting as a manufacturing method for integrating two different plastics, the extension of two-component injection moulding (2C-IM) from pure plastics to more resistant materials like ceramics or metals (2C-PIM) provided sophisticated and challenging applications. With the transfer of 2C-PIM to micro systems, two-component micro powder injection moulding (2C-MicroPIM) was established. Up to a certain extend sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For example, Imgrund et al (2007) and Imgrund et al (2008) reported on using two-component metal micromoulding to produce multifunctional micro-metallic components with reduced assembly steps. Ruh et al (2008) presented a similar approach to for two-component moulding and sinter joining in powder micromoulding, including a method to produce partially enclosed cavities by sinter joining to sub-components together (Ruh et al, 2011). Piotter et al (2010) and Piotter et al (2011) reported on another variant of powder micromoulding by which complex-shaped ceramic components could be produced.…”
Section: Debinding and Sinteringmentioning
confidence: 96%
“…For example, Imgrund et al (2007) and Imgrund et al (2008) reported on using two-component metal micromoulding to produce multifunctional micro-metallic components with reduced assembly steps. Ruh et al (2008) presented a similar approach to for two-component moulding and sinter joining in powder micromoulding, including a method to produce partially enclosed cavities by sinter joining to sub-components together (Ruh et al, 2011). Piotter et al (2010) and Piotter et al (2011) reported on another variant of powder micromoulding by which complex-shaped ceramic components could be produced.…”
Section: Debinding and Sinteringmentioning
confidence: 96%